Maple Syrup Urine Disease with Concomitant Congenital Adrenal Hyperplasia in a Setting of Consanguineous Marriage. - Hafiz Armaghan Saeed, Hamza Ismaeel, Hafiz Farzaan Saeed, Valeed Bin Mansoor (Journal of Rawalpindi Medical College, 2018)
Consanguineous marriage is deeply embedded in the fabric of South-East Asian society. Maple Syrup Urine Disease (MSUD) and congential adrenal hyperplasia (CAH) are autosomal recessive diseases, with an increased risk of transmission amongst progeny of consanguineous relationships. Maple syrup urine disease (MSUD) is an autosomal-recessive disorder of branched-chain amino acid (BCAA) metabolism, namely leucine, isoleucine and valine. It is rare in most populations occurring in about 1 in 185,000 live births.1 Deficiency of branched chain keto acid dehydrogenase(BCKD) results in accumulations of the aforementioned AAs, allo-isoleucine and alpha-ketoisocaproic acid (aKIC), resulting in cerebral edema and encephalopathy.Classic sign is “Burnt Sugar” or “Maple Syrup” smell in urine due to Alpha-Hydroxy Acid .